Neurotropic Effect of Botulinum Toxin and the Potential of Specific Serum Therapy in Botulism (Review) - E. M. Eliseeva; I. A. Mazerkina; A. A. Chistokhina (Безопасность и риск фармакотерапии, 2024)
INTRODUCTION. The outbreak of foodborne botulism that occurred in Russia in June 2024 once again demonstrated the danger of this rather rare but severe infectious disease caused by ingesting botulinum neurotoxin. The only aetiological treatment for botulism is currently the administration of antitoxins against various serotypes of botulinum toxin. However, antitoxins do not provide rapid regression of neurological symptoms, which may raise doubts about the effectiveness of the selected treatment option. It is impossible to assess the potential of specific treatment without understanding the mechanisms of action of botulinum toxin and antitoxin.AIM. This study aimed to systemise information on the mechanism underlying the damaging effect of botulinum neurotoxin, aetiological antitoxin treatment, and the patient recovery process.DISCUSSION. The mechanism underlying the damaging effect of botulinum neurotoxin consists in the destruction of SNARE proteins in presynaptic cholinergic nerve terminals, which disrupts the release of acetylcholine into the synaptic cleft and the transmission of excitation between neurons. The lack of acetylcholine at the neuromuscular junction results in a distinctive form of persistent flaccid paralysis. The specific mechanism of action of botulinum toxin determines the treatment strategy, which includes a set of life-sustaining measures and the earliest possible antiserum administration. If used within 48 hours from the onset of symptoms, botulinum antitoxin binds botulinum toxin circulating in the blood, which stops the progression of paralysis and prevents further disorders in patients. However, botulinum antitoxin cannot neutralise the effect of the toxin that has already bound to nerve receptors, so clinical symptoms may worsen within 12 hours after antiserum administration. Restoration of normal neuronal transmission occurs through the formation of new axonal sprouts and can take a long time.CONCLUSIONS. Antitoxin administration is effective and irreplaceable in the aetiological treatment of botulism. Nevertheless, the duration of recovery depends on the speed of reinnervation and restoration of transmission at the neuromuscular junction.